Description of a new species and species-group of Sphaeropthalma Blake Hymenoptera: Mutillidae) with an updated classification of the genus - Pitts, James P.; Sadler, Emily A. (Zootaxa, 2015)
A study of Sphaeropthalma Blake from the southwestern USA has revealed a highly autapomorphic undescribed species. This species is described here as S. tapio Pitts & Sadler, sp. nov., and is placed in a new species-group, the S. tapio species-group. This species seems to be found only at higher altitudes in southern Arizona. It is compared to other similar Sphaeropthalma species-groups and is likely most closely related to members of the S. imperialis species-group. An updated species-group classification of Sphaeropthalma is provided.